2005
DOI: 10.1007/s11258-004-0017-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of interspecific competition in perennial plants using Life Table Response Experiments

Abstract: The impact of interspecific competition is usually measured by its effect upon plant growth, neglecting impacts upon other stages of the life cycle such as fecundity which have a direct influence upon individual fitness and the asymptotic population growth rate of a population ͑͒. We used parameterized matrix models for three perennial plant species grown with and without interspecific competition to illustrate how the methodology of Life Table Response Experiments ͑LTRE͒ can be used to link any change in pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 22 publications
4
39
0
Order By: Relevance
“…Length of stem did not significantly vary between years and treatments. This corresponds to the findings of Fréville and Silvertown (2005), who reported that interspecific competition mainly affects fecundity, which is recognised by a decreasing number of flowers, fruits and seeds per fruit. Our results are also in line with that of Partzsch et al (2010) who revealed that F. rupicola negatively affects flower and seed production of the rare, lowgrowing Alyssum montanum.…”
Section: Performance Of Plant Parameterssupporting
confidence: 91%
“…Length of stem did not significantly vary between years and treatments. This corresponds to the findings of Fréville and Silvertown (2005), who reported that interspecific competition mainly affects fecundity, which is recognised by a decreasing number of flowers, fruits and seeds per fruit. Our results are also in line with that of Partzsch et al (2010) who revealed that F. rupicola negatively affects flower and seed production of the rare, lowgrowing Alyssum montanum.…”
Section: Performance Of Plant Parameterssupporting
confidence: 91%
“…In addition to biomass development -which was only slightly affected -the presence of F. rupicola had a considerable negative effect on several quantitative parameters of A. montanum fitness, such as number of fruits. The assumption that plant fecundity is often more severely affected by interspecific competition than survival and growth was also verified by Fréville and Silvertown (2005) in a comparative study on grassland species. Our data contrast those of Bachmann et al (2005), who even reported a facilitation of the rare Campanula glomerata by the same grass species F. rupicola.…”
Section: Discussionmentioning
confidence: 87%
“…The use of demographic tools is a promising way to study such plant interactions and their consequence at the population and community level. For example, ''Life table response experiments'' have been used to detect the effect of competition on plant vital rates and how vital rates affect population growth rate (Freville and Silvertown 2005). We strongly advocate the integration of individual-based processes in further studies of population and community organisation.…”
Section: Discussionmentioning
confidence: 99%